Integration of vole management in boreal silvicultural practices1. Issue 3 (27th February 2012) - Huitu, Otso; Rousi, Matti; Henttonen, Heikki
Abstract Voles of the genera Microtus and Myodes are widespread and among the most abundant of small mammal species in the boreal zone of the Northern Hemisphere. They are keystone herbivore species in northern ecosystems, and they have profound impacts on both higher and lower trophic levels. Voles are also major silvicultural pests, damaging millions of tree seedlings in years of peak abundance. Prevention of vole damage to silviculture has proven to be very difficult owing to the ubiquity of both suitable vole habitat and potential damage sites across landscapes. The degree of damage inflicted by voles on seedling stands is largely, but not solely, determined by prevailing vole densities, which often fluctuate in 3–4 year population cycles. Silvicultural practices related to site habitat manipulation and/or choice and rearing of seedling material may also greatly influence the severity of vole damage to seedlings. The manipulation of these practices is currently at the forefront of methods potentially applicable to control vole damage in boreal forests. This paper reviews current evidence for the efficacy and present recommendations for further development and application of these methods to mitigate vole damage to seedling stands in boreal silviculture. © 2012 Society of Chemical Industry